Reactive programming with JavaScript : learn the hot new frontend web framework from Facebook--ReactJS, an easy way of developing the V in MVC and a better approach to software engineering in JavaScript /: learn the hot new frontend web framework from Facebook--ReactJS, an easy way of developing the V in MVC and a better approach to software engineering in JavaScript. (2015) - Hayward, C.J.S, 1975-
No abstract available